Effect of different feeds on growth, survival and production of freshwater mud eel, Monopterus cuchia (Hamilton) - Narejo, N T; Rahmatullah, S M; Rashid, M Mamnur (Indian Journal of Fisheries, 2011)
An experiment was conducted to study the effect of different feeds on growth,survival and production of freshwater mud eel, Monopterus cuchia reared incemented cisterns (1.25m2 each) over a period of twelve months from July 2000to June 2001. Three different feeds namely F 1(live small fish), F 2 (dead smallfish) and F 3 (pellet feed, 30% protein) were applied to treatment I, II and IIIrespectively. Each cistern was stocked with ten fish having mean initial bodyweight of 30.5 Â± 4.25 g, each treatment was replicated thrice. Highest weightgain of 71.20 Â± 3.78 g was obtained in treatment II (p